Identifying key intermediates for the oxygen evolution reaction on hematite using ab-initio molecular dynamics - Shuai Xu; Jiarui Yang; Peixian Su; Qiang Wang; Xiaowei Yang; Zhaohui Zhou; Yuliang Li (Nature Communications)
Abstract Hematite is a well-known catalyst for the oxygen evolution reaction on photoanodes in photoelectrochemical water-splitting cells. However, the knowledge of hematite-water interfaces and water oxidation mechanisms is still lacking, which limits improvements in photoelectrochemical water-splitting performance. Herein, we use the Fe-terminated hematite (0001) surface as a model and propose a comprehensive mechanism for the oxygen evolution reaction on both non-solvated and solvated surfaces. Key reaction intermediates are identified through ab initio molecular dynamics simulations at the density functional theory level with a Hubbard U correction. Several notable intermediates are proposed, and the effects of water solvent on these intermediates and the overall reaction mechanisms are suggested. The proposed mechanisms align well with experimental observations under photoelectrochemical water oxidation conditions. Additionally, we highlight the potential role of O2 desorption in the oxygen evolution reaction on hematite, as O2 adsorption may block reaction sites and increases surface hydrophobicity, leading to an unfavorable pathway for oxygen evolution.